The history of the Kazakh written signs - Akhmediyeva K, Ybyraimzhanov К, Bekish A, Mailybaeva G, Shengelbayeva S, (Opción, 1970)
This article discusses the primary education systems on Kazakhland and the history of written signs, and alphabets based on systemdescriptions via analysis from a philosophical, historical, sociopoliticaland pedagogical-psychological point of view. As a result, Activitiescarried out in Kazakhstan to translate the Kazakh script into the Latinalphabet, were ill-conceived, they did not solve the problem of theKazakh alphabet, and it was evident from the experience. Inconclusion, there was a reform of the Kazakh script in the system oforganization of the educational process in primary school.